Robotic-assisted versus conventional laparoscopic hysterectomy for endometrial cancer - Cherynne Yuin Mun Johansson; Felix Kwok Hee Chan (Elsevier, 2020)
Objective: The safety and efficacy of robotic-assisted laparoscopic hysterectomy (RALH) compared with conventional total laparoscopic hysterectomy (TLH) for surgical staging of endometrial cancer has not been clearly established. With the commencement of a robotic program at our institution, our objective was to evaluate and compare the surgical outcomes of RALH with TLH for endometrial cancer. Methods: A retrospective cohort study was performed on 39 patients who underwent RALH and 41 patients who underwent TLH for endometrial cancer at a tertiary care academic institution. Results: In the setting of endometrial cancer RALH is significantly longer to perform than TLH (mean operating time 133 min vs 107 min, p = 0.0001). There is higher estimated blood loss in TLH cases than RALH cases (78 mL vs 22 mL, p = 0.015). Women who underwent RALH had a shorter length of stay (1.3 days vs 1.8 days, p = 0.006) than TLH patients, and six cases (15 %) of the RALH group were discharged on the same day of surgery. There were no differences between the RALH and TLH groups in intraoperative or postoperative complications and there were no conversions to laparotomy. Conclusion: RALH is safe and feasible for the treatment of endometrial cancer, with low morbidity, less blood loss and shorter length of stay than TLH. RALH is associated with longer mean operating times than TLH and this may improve with enlisting a consistent experienced team. Prospective randomised studies which include analysis of quality of life measures and long-term outcomes are required to further establish the role of RALH in the surgical staging of endometrial cancer.